Critical reflection on knowledge and narratives of conservation agriculture. (March 2015) - Whitfield, Stephen; Dougill, Andrew J.; Dyer, Jen C.; Kalaba, Felix K.; Leventon, Julia; Stringer, Lindsay C.
Highlights: A review of the recent history of conservation agriculture in Zambia. Interprets the changing politics and knowledge driving investments into the scaling up of this agricultural technology. Identifies knowledge gaps and assumptions within success claims. Discusses the importance of evidence and narratives in shaping trajectories of agricultural change. Abstract: In the context of contemporary concerns about climate change and food security, Conservation Agriculture (CA) has emerged as a well-supported and central component of the agricultural sector development strategy across sub-Saharan Africa, including in Zambia, which is the focus of this paper. A variety of narratives about the benefits of CA over conventional agricultural systems underpin endeavours towards 'scaling up' CA and increasing rates of adoption amongst smallholder farmers nationwide. However, there is a knowledge politics underlying the translation of a weak evidence base around CA into persuasive narratives and financial and political support. In this paper, we trace the evolution of five narratives around CA in Zambia in relation to changing political agendas and the involvement of new public and private sector actors, and review the development of evidence bases and knowledge that support and challenge each of these narratives. We discuss the potential to open up space within this knowledge politics to alternative narratives and the contestation of the pervasive CA scaling up agenda. Critical reflection is essential to ensure that national and local evidence is more effectively used to guide national climate and agricultural policy developments and international donor initiatives.